Effect of Adding the White Legged Shrimp (Penaeus vannamei) on Growth and Survival of Tiger Shrimp (Penaeus monodon) in Intensive Farming - Tarsim, . (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
This experiment was carried out in the framework of a project to develop a viable shrimp polyculture technology under intensive farming. The objectives were to assess the effect of adding white legged shrimp (Penaeus vannamei) on growth and survival of tiger shrimp (Penaeus monodon) in intensive Farming. Tiger shrimp were stocked in 2800-3400 m2 earthen ponds at 40 individuals/m2 and reared for 133 days. White legged shrimp added at 70 day at 8±2 individuals/m2. Growth rate and total yield affected by addition of this species. Final affected by white legged shrimp addition. No adding effects were found on the water quality parameters. The results indicate that, at densities tested, white legged shrimp addition to the intensive farming of tiger shrimp polyculture is viable as species increase crop production Key words: Penaeus vannamei, P. monodon, growth, survival, polyculture